(untitled) (Annals of Medical Research, 2023)
Aim: Chest pain is the second reason of admissions to the emergency department (ED) after injury. In this study it was aimed to make a perspective by examining scientific manuscripts published on chest pain from an emergeny medicine perspective with statistical methods. Materials and Methods: Exploratory and descriptive bibliometric study conducted in Ankara, Turkey. Database of Web of Science (WoS) was the source of this study. The articles indexed between the years 1980 and 2022 were included. The manuscripts of the current year (2023) were excluded because the factors affecting it were not yet clear. “Chest Pain” were the used keyword in searching the articles. Results: By analyzing the WoS database using the term "chest pain", we arrived at a total of 3,329 publications. When the citations of the documents written about chest pain were evaluated, we detected that in 2021 more citations were made than the other years. Co-citation analysis showed 11,310 authors researching the topic of chest pain. Collaboration and citation collaboration has been observed between Duke University, Harvard University, and the Mayo Clinic. Coronary artery disease and acute coronery syndrome were found the strongest relationship with chest pain. Conclusion: It is observed that publications on chest pain are associated with acute coronary syndrome (ACS) and this diagnosis has the highest publication, citation and impact power. The number of publications on other fatal clinical conditions presented with chest pain is relatively low.